Efficacy and safety of a skin healing cream in mild-to-moderate eczema in a mixed population including infants: An open-label, single-arm study - Shilpa Dhar; Trupti Patel; Arohi Bapna; Govindarajan Raghavan (Wolters Kluwer Medknow Publications, 2023)
Introduction: Atopic dermatitis is an inflammatory skin condition that begins in infancy, characterized by extreme skin dryness, excoriations, and erythema. A completely natural product with plant extracts and vegetable oils was developed to manage eczema and associated conditions in a mixed population including infants. Materials and Methods: An open-label, single-arm, single-center study was conducted to evaluate the safety and efficacy of the test product on eczema severity. A total of 58 subjects, including infants, children, and adults aged 0 months to 60 years, diagnosed with mild-to-moderate eczema, were included. The subjects applied a small amount of product on the affected area twice daily for 14 days. Three-Item Severity (TIS) score, Eczema Area and Severity Index (EASI) change, and symptomatic relief were assessed at various time points. Results: The TIS score in children significantly reduced from baseline at 24 h (12.22%), day 7 (52.26%), and day 14 (79.74%), (all P <0.0001). Similarly, a statistically significant reduction in EASI was observed in adults at day 7 (13.68%) and day 14 (30.87%) (all P < 0.0001), which continued to offer relief throughout the study duration. Irritation significantly decreased from baseline throughout the study duration to day 14 (75.17%) (P < 0.0001). A significant reduction in other symptoms including dryness, itching, rashes, and edema was also seen from day 7 to day 14 (P < 0.0001). Conclusion: The test product was found to be safe and effective in reducing eczema severity and associated conditions in infants and adults. It promotes the development of healthy neonatal skin and hence can be considered as a skin-healing cream for infants.